The photoelectron spectrum of ethylene oxide adsorbed at metal surfaces: a density functional model cluster study of C2H4O Ni(110) - Ulbricht, P.; Häberlen, O.D.; Weinelt, M.; Steinrück, Hans-Peter; Rösch, Notker (Surface Science, 1995)
The electronic structure of ethylene oxide adsorbed at Ni(110) has been calculated by the LCGTO-DF method using cluster models of various adsorption sites. At the local density level of theory a weak binding of the adsorbate to the substrate is found, but a repulsive interaction results for a gradient corrected energy functional. No major differences are calculated between the one-electron level spectrum of gas phase and of adsorbed ethylene oxide molecules. A new assignment of the photoelectron spectrum of ethylene oxide adsorbed at metal surfaces is proposed which differs from previous experimental and theoretical investigations of ethylene oxide adsorbed at various metal surfaces. © 1995.